Veterinary histology of domestic mammals and birds: Textbook and Colour Atlas. - Liebich, Hans-Georg (5m Publishing, 2019)
Provides a comprehensive study of the microscopic structure of tissues and organs in domestic mammals and birds, linking histological features with their functions. It includes detailed color atlas illustrations, micrographs, and essential concepts for veterinary anatomy, histology, and clinical practice.